"The innovation governance dilemma: Alternatives to the precautionary principle". (November 2020) - Hemphill, Thomas A.
Abstract: This article reviews the four innovation governance approaches (the precautionary principle, responsible innovation, permissionless innovation, and the innovation principle), including definitions, important attributes, and weaknesses found in each approach, and when utilizing an affinity diagram as a tool of analysis, identifies their distinctive characteristics and common relationships. A discussion section summarizes the paper's findings and offers insights into where there is common relationships for further possible convergence between two innovation governance approaches – responsible innovation and permissionless innovation – that conceptually share substantially more in common than they contrast with each other. For addressing this challenge, the study recommends the following policy proposals: embrace artificial intelligence/machine learning/data analytics for risk management and regulatory adaptability; consider "soft law"as an option to public regulation; and substitute corporate citizenship for corporate social responsibility. Highlights: Innovation governance approaches: precautionary principle, responsible innovation, permissionless innovation, innovation principle. Conceptual components unique to each innovation governance approach were identified and then compared across approaches. The responsible innovation and permissionless approaches conceptually share substantially  more  in common than contrast. To close the conceptual "gap" between these two similar innovation governance approaches, the study recommends three policy proposals.